Influence of consumers' brand expectations on apparel brands' US-based sourcing strategy. Issue 1 (9th January 2017) - Bhaduri, Gargi
Abstract : Purpose: This study aims to understand how consumers evaluate Made in USA messages that are congruent/incongruent to consumers' prior expectations about the brand's US-based sourcing initiatives. Design/methodology/approach: Two separate studies were conducted. Online experiment was designed implementing both message and treatment variance to increase internal and external validity of the study. Data collected from two distinct samples were analyzed using MANOVA and ANOVA. Findings: Findings from Study 1 indicated that consumers' perceived message credibility, attitude toward message and attitude toward brand were highest for congruent messages, followed by when incongruity was resolved and lowest when incongruity was not resolved. Further, consumers' brand attitudes before and after message exposure were different, with change being most positive for incongruity resolution, followed by congruity, whereas negative for incongruity non-resolution. Findings from Study 2 indicated that consumers' general attitude toward brands' US-based sourcing strategies influenced their brand attitude, as well as moderated the relation between schema congruity/incongruity resolution/incongruity non-resolution and brand attitude. Originality/value: The findings are helpful for brand managers and sourcing personnel to better invest their resources in US-based sourcing strategies. In addition, the findings of the study contribute and extend theory by identifying a boundary condition.